High-Carbohydrate Diet Enhanced the Anticontractile Effect of Perivascular Adipose Tissue Through Activation of Renin-Angiotensin System - Reis Costa, Daniela Esteves Ferreira dos; Silveira, Ana Letícia Malheiros; Campos, Gianne Paul; Nóbrega, Natália Ribeiro Cabacinha; de Araújo, Natália Ferreira; de Figueiredo Borges, Luciano; dos Santos Aggum Capettini, Luciano; Ferreira, Adaliene Versiani Matos; Bonaventura, Daniella (Frontiers in Physiology, 2021)
The perivascular adipose tissue (PVAT) is an active endocrine organ responsible for release several substances that influence on vascular tone. Increasing evidence suggest that hyperactivation of the local renin-angiotensin system (RAS) in the PVAT plays a pivotal role in the pathogenesis of cardiometabolic diseases. However, the local RAS contribution to the PVAT control of vascular tone during obesity is still not clear. Since the consumption of a high-carbohydrate diet (HC diet) contributes to obesity inducing a rapid and sustained increase in adiposity, so that the functional activity of PVAT could be modulated, we aimed to evaluate the effect of HC diet on the PVAT control of vascular tone and verify the involvement of RAS in this effect. For that, male Balb/c mice were fed standard or HC diet for 4 weeks. Vascular reactivity, histology, fluorescence, and immunofluorescence analysis were performed in intact thoracic aorta in the presence or absence of PVAT. The results showed that HC diet caused an increase in visceral adiposity and also in the PVAT area. Phenylephrine-induced vasoconstriction was significantly reduced in the HC group only in the presence of PVAT. The anticontractile effect of PVAT induced by HC diet was lost when aortic rings were previously incubated with angiotensin-converting enzyme inhibitor, Mas and AT2 receptors antagonists, PI3K, nNOS and iNOS inhibitors, hydrogen peroxide decomposing enzyme or non-selective potassium channels blocker. Immunofluorescence assays showed that both Mas and AT2 receptors as well as nNOS and iNOS isoforms were markedly expressed in the PVAT of the HC group. Furthermore, the PVAT from HC group also exhibited higher nitric oxide and hydrogen peroxide bioavailability. Taken together, these findings suggest that the anticontractile effect of PVAT induced by HC diet involves the signaling cascade triggered by the renin-angiotensin system through the activation of Mas and AT2 receptors, PI3K, nNOS and iNOS, leading to increased production of nitric oxide and hydrogen peroxide, and subsequently opening of potassium channels. The contribution of PVAT during HC diet-induced obesity could be a compensatory adaptive characteristic in order to preserve the vascular function.